The divine Marquis' ethical project: Sade and the "turn to religion" in postmodernist philosophy - Russell, Melissa Michele (Curtin University, 2014)
This thesis argues that Sade’s work constitutes a transgressive ethical project that cannot escape Christian ethical categories. According to the logic of transgression Sade must invoke and reinstate those limits and categories – such as good/evil, vice/virtue, sacred/profane – that he destroys. I do not argue that Sade employed a theory of transgression but, following Bataille and Foucault, who base their concept of transgression on Sade’s work, I use transgression as a philosophical lens through which to reread him.